2019
DOI: 10.1016/j.mod.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish otolith biomineralization requires polyketide synthase

Abstract: Deflecting biomineralized crystals attached to vestibular hair cells are necessary for maintaining balance. Zebrafish ( Danio rerio ) are useful organisms to study these biomineralized crystals called otoliths, as many required genes are homologous to human otoconial development. We sought to identify and characterize the causative gene in a trio of homozygous recessive mutants, no content ( nco ) and corkscrew ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Another PKS characterized by genetic means, but with uncertain products, is OlPKS found in the zebrafish. Nonsynonymous mutation in the OlPKS KS domain led to deficiencies in otolith (hearing) formation in the fish and is related to calcium accumulation (36). This function is conceptually similar JBC REVIEWS: The biosynthetic diversity of the animal world to the role of Pks2 result from urchins.…”
Section: Polyketide/fatty Acid Metabolismmentioning
confidence: 94%
See 1 more Smart Citation
“…Another PKS characterized by genetic means, but with uncertain products, is OlPKS found in the zebrafish. Nonsynonymous mutation in the OlPKS KS domain led to deficiencies in otolith (hearing) formation in the fish and is related to calcium accumulation (36). This function is conceptually similar JBC REVIEWS: The biosynthetic diversity of the animal world to the role of Pks2 result from urchins.…”
Section: Polyketide/fatty Acid Metabolismmentioning
confidence: 94%
“…In the course of these studies, the investigators identified many other PKSs in animals of many different phyla, showing that animal PKSs are widespread (33,34,36,38). Intriguingly, whereas the domain order of the PKS is somewhat conserved at the protein N terminus, the C-terminal ends of animal PKSs are highly variable, containing different termination domains, and even in several cases NRPS domains.…”
Section: Polyketide/fatty Acid Metabolismmentioning
confidence: 99%
“…Otolith precursor particles are initially found distributed throughout the otic vesicle lumen, but adhere specifically to the tips of kinocilia on the first hair cells to differentiate in the ear (named tether cells for this reason) [2,3,9]. The composition of the particles has not been fully described, but they are likely to contain Cadherin11 [40], Otoconin90 [41,42] and Starmaker [43,44]. At the kinociliary tip, the bound otolith precursor particles serve as a nucleation site for deposition of further layers of protein and mineral (calcium carbonate), and thus the tether kinocilia become partially embedded within the structure of the otolith.…”
Section: The Role Of Zebrafish Otic Cilia In Otolith Formationmentioning
confidence: 99%
“…At the kinociliary tip, the bound otolith precursor particles serve as a nucleation site for deposition of further layers of protein and mineral (calcium carbonate), and thus the tether kinocilia become partially embedded within the structure of the otolith. Efficient production or nucleation of the precursor particles, in both zebrafish and medaka, appears to require the activity of the enzyme polyketide synthase [41,45,46]. Growing zebrafish otoliths incorporate a number of proteins, including Otolith Matrix Protein-1, Sparc, Starmaker and others [47][48][49][50].…”
Section: The Role Of Zebrafish Otic Cilia In Otolith Formationmentioning
confidence: 99%
See 1 more Smart Citation